Habitat modeling of mature albacore (Thunnus alalunga) tuna in the Indian Ocean - Mondal, Sandipan; Lee, Ming-An (Frontiers in Marine Science, 2023)
This study examined the spatial distribution of mature albacore tuna (Thunnus alalunga) in the Indian Ocean between 1998 and 2016 (October to March) using environmental factors and logbook fishery data from Taiwanese longliners. We collected the albacore tuna fishery data, including fishing location, fishing effort, number of catch, fishing duration, and fish weight. The optimal limits for oxygen, temperature, salinity, and sea surface height for mature albacore tuna, as determined by generalized additive modeling, were 5–5.3 mL/L, 25–29°C, 34.85–35.55 PSU, and 0.5–0.7 m, respectively. The optimal models were determined to be a geometric mean–derived habitat suitability–based model constructed with oxygen, temperature, and salinity and a generalized additive model constructed with oxygen, temperature, salinity, and sea surface height. From October to March, mature albacore tuna remained between 10°S and 30°S. Our study concurs with previous studies on albacore tuna in the region that suggest that the spawning area is located between 10-25˚S, and that spawning occurs primarily between November and January. This study reveals the spatial patterns and environmental preferences of mature albacore tuna in the Indian Ocean which may help put in place better management practices for this fishery.